False Identity Detection Using Complex Sentences - Monaro, Merylin; Gamberini, Luciano; Zecchinato, Francesca; Sartori, Giuseppe (Frontiers in Psychology, 2018)
The use of faked identities is a current issue for both physical and online security. In this paper, we test the differences between subjects who report their true identity and the ones who give fake identity responding to control, simple and complex questions. Asking complex questions is a new procedure for increasing liars’ cognitive load, which is presented in this paper for the first time. The experiment consisted in an identity verification task, during which response time and errors were collected. Twenty participants were instructed to lie about their identity, whereas the other twenty were asked to respond truthfully. Different machine learning (ML) models were trained, reaching an accuracy level around 90-95% in distinguishing liars from truth tellers based on error rate and response time. Then, to evaluate the generalization and replicability of these models, a new sample of ten participants were tested and classified, obtaining an accuracy between 80% and 90%. In short, results indicate that liars may be efficiently distinguished from truth tellers on the basis of their response times and errors to complex questions, with an adequate generalisation accuracy of the classification models.